UK Research Excellence: Getting Better All the Time? - Marginson, Simon (International Higher Education, 2015)
An analysis of the recent Research Excellence Framework data, released in the UK in late 2014, this article critically evaluated this major program. The REF purports to measure research impact of UK universities and researchers, but often does not adequately measure what is important.